Defining Open Innovation Concept Using Business Process Modeling. (2016) - Banu, Geanina Silviana; Dumitrescu, Andreea; Purcărea, Anca Alexandra; Isărescu, Silviu Walter
Abstract: Present research explores the open innovation process through Business Process Modeling tools with the aim of emphasizing its characteristics alongside connected risks. Based on a thorough literature review, the authors have identified and described the sub-processes/activities of the open innovation model and depicted its core elements by using Bizagi software. The authors' conclusion is that important activities of open innovation are yet to be fully identified and analyzed as open innovation model represents an integrated inbound and outbound process.